Synthesis and Characterization of New ligand ’ ((2-1..,[(2-hyd_roxy;..benzyli_dene)-hydrazono]- ethyl benzen_e-l, 3, s–moll and ItComplexes WÂ·itll. (Mn.(11 Fe(n), Cd
In :the _pr sent _paper we report ths. ynthesis Â·of a new li:ga!!d.. [f4LJ [’2 1-’[(2-hydâ€¢:0xy-.ben:zy1i.denÂ·e)..,bxcJrazanci:etby-l benzerieÂ J,5 t;rtiol .aad its complexes Â·w-ith ’(’Mlif(1 J Fev 1 ), ed(J’l), and. :f.::I:g 01>-) The ligand preP..ated rin tWo steps’ â€¢ fp I t